The Effect of Law in the Transformation of the Urban Space as an Urbanization Strategy: The Case of Ankara - Bektas, Yasin (KARE PUBL, 2014)
Urban transformation projects in Turkey come up as a new urbanization project. Starting from the early 2000' s to the present day, several legal arrangements about urban transformation have been made. According to these regulations, delegated acting authority is increasingly centralized and urgency is becoming an integral parts of urban renewal process. As a result, same urban transformation projects are offered in Turkey's large metropolitan areas, especially in urban centers and areas with high rent value, causing local characteristics and local issues of these areas to be ignored in the process. In addition, with the facilities afforded by the law, authority to conduct urban transformation projects can be centralized on a single institution. In this study, urban transformation laws enacted after 2000' s, and these laws are examined regarding for which areas of the city Ankara. In the study, realization of urban transformation laws within the legal framework is discussed, legal issues are examined and authority transfers are identified. In the study, whether or not intended discourse like healthy and safe living environments renewed in accordance with norms of science and art... are real or truthful is determined. Urban transformation areas in the province of Ankara include urban transformation projects completed between 2000 and 2014, projects in the implementation stage and projects in the announcement stage
Keywords: Urban transformation laws; risky area; urban transformation; participation; planning; Public Administration